2022
DOI: 10.1002/jsf2.80
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of biogas production and bacterial load from manure of layer chicken fed with two different types of feed

Abstract: Background: The focus of this research was to assess the biogas production of Chicken Manure (CM) collected from hybrid layer chickens fed non-commercial (CMNC) and commercial (CMC) feed, as well as to evaluate the bacterial load of feeding stock and digested slurry samples before and after Anaerobic Digestion (AD). The effects of the feedstock and digestion composition of CM on biogas production were measured. The experiment was carried out utilizing lab-based proto-type digesters for CM with or without inocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…This could be attributable to the low VS content (% of TS) of the substrate in the T1 group, where the average concentration of CH 4 was marginally lower. In mono‐digestion of CM, the average concentrations of CH 4 and CO 2 in biogas were 46%–58% and 42%–54%, respectively, as reported by Haque et al 14 Elasri and El amin Afilal 35 reported that the AD of CM produced biogas containing at least 60% methane and 39% carbon dioxide.…”
Section: Resultssupporting
confidence: 56%
See 4 more Smart Citations
“…This could be attributable to the low VS content (% of TS) of the substrate in the T1 group, where the average concentration of CH 4 was marginally lower. In mono‐digestion of CM, the average concentrations of CH 4 and CO 2 in biogas were 46%–58% and 42%–54%, respectively, as reported by Haque et al 14 Elasri and El amin Afilal 35 reported that the AD of CM produced biogas containing at least 60% methane and 39% carbon dioxide.…”
Section: Resultssupporting
confidence: 56%
“…For group T3, which produced the highest methane yield, the C:N ratio of 17:1 was within the optimal range 31 . Compared with CM mono‐digestion, the fertilizer values (N, P, K, and S) of digestion were found to be slightly higher 14 . All groups' VFA concentrations fell within the permissible range of 384–674 mg/L (Table 4).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations